ENT600: Smart Water Hose / Muhammad Heedir Shamsul Kamar, Mohd Jawahir Ahmad Ramli and Ahmad Fuad Omar - Shamsul Kamar, Muhammad Heedir; Ahmad Ramli, Mohd Jawahir; Omar, Ahmad Fuad (2017)
What do we expect to see towards the year 2020? A flying car, a human-like robot or a hoverboard? Frankly, we do not think, that is what we need in 2020 after all but, what we should expect is a cleaner, tidier and more hygienic toilet. Toilet hygiene and tidiness always being overlooked and not taken seriously. The current toilet design will not be discussed further, however, the person's experience and practicing behaviour with the toilets environment itself are the primary focus here. Toilets facilities are available in many countries. Variety of toilets design, different flushing systems or flushing mechanism exists. Cleansing facilities such as water taps and hose supply, toilet papers and hand dryer equipped inside the toilets (Hamid, Toyong, & Rahman, 2016). However, the user's behaviour and lack of awareness often make toilet become unhealthy. In our observation in FSK, UiTM Puncak Alam, at least one out of three toilet stall water hose on every floor is not place correctly on it place. The water hose is left on the floor. More aggravating condition, some of the toilet stall left the water pipe open. This situation can lead to a bigger problem soon. For example, if the water hose is left on the floor, the bacterial growth will take place and this can generate unpleasant smell (Barbosa & Thompson, 2016). Plus, unclose water pipe can promote water wastage and this condition is very inflict a financial cost. So, our company come with the idea of "Smart Water Hose" in order to tackle this problem. However, throughout the project, we faced some limitation for example we lack of expertise in sales marketing. We are looking forward to add someone who is expert in marketing to our team to improve our product sales in the future.